Local Movements, Political Processes and Transformation: A Case Study of Bhaktapur Municipality - Dhakal, Suresh; Pokharel, Sanjeev (Occasional Papers in Sociology and Anthropology, 2010)
The people of Nepal have witnessed a number of political shifts within a comparatively short period of the country's history. The political revolution of 1950, which precedes all important political movements, eliminated the century-long Rana oligarchy and established the multiparty system. In 1960, late King Mahendra abolished the newly established multi-party system and implemented his own model of governance called the Panchayat system. The Panchayat system was designed to allow the King to rule the country according to his will, and the system alienated ordinary people from political processes. This system, too, came to an end after the popular movement of 1990 (widely known as jana andolan) which re-established the multi-party system in the country. DOI: 10.3126/opsa.v11i0.3036 Occasional Papers in Sociology and Anthropology Vol.11 2009 178-201